Spejlets gåde - Albinus, Lars (Dansk Teologisk Tidsskrift, 2011)
In this article the point of departure for presenting a hermeneutic reading of Augustine’s Confessiones is taken in St. Paul 1 Cor. 13:12 where Paul speaks of our being earthly conditioned to see everything in a mirror as if in a riddle until we stand face to face with our creator. In a selective reading of Confessiones, I argue that the book is structured in a two layered manner in which the relationship between Augustine and his earthly parents is transposed to a relationship between these relatives, on the one hand, and their heavenly parents in God and his church, on the other. I further argue that Augustine’s individual life story in a similar vein gains its fulfilment in the creation and consummation of the world. Thus, in the concluding exegesis of the introducing verses of Genesis, in which God’s concreatio of time and matter mirrors human existence, Augustine unfolds the prospect of a totality only to be grasped face to face with the creator, that is, in the eschatological revelation of the love of God.